Time Periodic Varying Deceleration Parameter in Reconstructed f(R,T) Gravity - , Can Aktaş; , Sezgin Aygün (Archives of Current Research International, 2017)
In this paper, we have investigated a string cloud with perfect fluid matter distributions for Friedmann–Robertson–Walker (FRW) space-time in reconstructedƒ(R,T) = α1R + α2ƒ3(T) gravity. To obtain exact solutions of the field equations we have used a time periodic varying deceleration parameter. The new reconstructed f(R,T) model includes two models of Harko et al. and transforms to general relativity. However, we obtain vanishing string tension density in all models. This result agrees with Aygün and colleagues, Naidu et al. and Kiran and Reddy in different alternative gravitation theories.